The Canadian–U.S. Exchange Rate: Evidence from a Vector Autoregression - Backus, David (The Review of Economics and Statistics, 1986)
A vector autoregression is used to elicit the empirical facts co ncerning exchange rate movements. The author finds (1) the exchange rate, relati ve price levels, and trade balances are closely related;(2) most other lagged v ariables have no perceptible influence in theexchange rate equation; (3) exchan ge rate innovations are negativelycorrelated with innovations in output and pri ces, positively with innovations in the balance of trade, and almost not at all with innovations in money; and (4) impulses in money, trade balances, and govern ment spending are followed by opposing future movements in theexchange rate and the price level. Taken as a whole, the evidence suggests that exchange rate cha nges may be associated with real, rather than monetary, shocks. Copyright 1986 by MIT Press.